2021
DOI: 10.3390/ijerph18073598
|View full text |Cite
|
Sign up to set email alerts
|

Abbreviated MRI Protocol for the Assessment of Ablated Area in HCC Patients

Abstract: Background: Liver Imaging Reporting and Data Systems (LI-RADS) Treatment Response Algorithm (TRA) was created to provide a standardized assessment of hepatocellular carcinoma (HCC) following loco regional therapy. The aim of this study was to compare sensitivity of standard MRI protocol versus abbreviated protocol (only T1-Weigthed fat suppressed (FS) sequences pre- and post-contrast phase) in the detection of ablated area according to LI-RADS Treatment Response (LR-TR) categories. Methods: From January 2015 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 34 publications
(55 reference statements)
0
27
0
Order By: Relevance
“…Specifically, studies that reported on the performance of LR-TR viable category but did not report data on the performance of each imaging feature were excluded [18][19][20]. Finally, a total of 10 eligible articles reported the diagnostic performance of LR-TR viable features for diagnosing viable HCC (Table 1) [11][12][13][14][21][22][23][24][25][26]. Of the 10 eligible articles, 10 reported the performance of NMLIT with APHE [11][12][13][14][21][22][23][24][25][26], 8 reported that of NMLIT with washout appearance [11][12][13][14][22][23][24][25], and 6 reported that of NMLIT with enhancement similar to pretreatment [12][13][14]22,23,25].…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, studies that reported on the performance of LR-TR viable category but did not report data on the performance of each imaging feature were excluded [18][19][20]. Finally, a total of 10 eligible articles reported the diagnostic performance of LR-TR viable features for diagnosing viable HCC (Table 1) [11][12][13][14][21][22][23][24][25][26]. Of the 10 eligible articles, 10 reported the performance of NMLIT with APHE [11][12][13][14][21][22][23][24][25][26], 8 reported that of NMLIT with washout appearance [11][12][13][14][22][23][24][25], and 6 reported that of NMLIT with enhancement similar to pretreatment [12][13][14]22,23,25].…”
Section: Literature Searchmentioning
confidence: 99%
“…Finally, a total of 10 eligible articles reported the diagnostic performance of LR-TR viable features for diagnosing viable HCC (Table 1) [11][12][13][14][21][22][23][24][25][26]. Of the 10 eligible articles, 10 reported the performance of NMLIT with APHE [11][12][13][14][21][22][23][24][25][26], 8 reported that of NMLIT with washout appearance [11][12][13][14][22][23][24][25], and 6 reported that of NMLIT with enhancement similar to pretreatment [12][13][14]22,23,25].…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…In this setting, imaging observations depend highly on the type and the method of therapy delivery, the timing of treatment, and the imaging technique being used to observe the effects. Therefore, an evaluation based only on dimensional data is not appropriate to assess the efficacy of such complex treatments, since not always a positive response to treatment is linked to a size reduction; furthermore dimensional criteria do not allow the differentiation of the fibrotic tissue from the residual tumor [ 218 ]. The LI-RADS treatment response algorithm applies to multiphase CT or MRI used to assess response after local-regional therapy, which includes percutaneous therapy (eg, ethanol and radiofrequency or microwave ablation), transcatheter therapy (eg, transarterial chemoembolization or radioemboliza- tion), and external beam radiation therapy.…”
Section: Discussionmentioning
confidence: 99%